(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
Based on the discourse analysis of a corpus composed of documents and reports both official and civil society organizations, presidential speeches and published news, this paper summarizes some of the main mechanisms and discourses that have been used by the Colombian state to narrate the violent past of the country. The proliferation of expert commissions is discussed and we put special attention on the creation of the National Historical Memory Center as a way to respond to the “duty of memory of the state”, typified and modified in two central laws for the treatment of armed actors and the and the guarantee of the rights victims who have left more than decades of armed conflict in the country. Finally, we examine some of the divergent positions that have been held by the last three governments and the effects in the public sphere of these disputed versions of the past, trying to demonstrate that there is a growing interest in the way in which this is narrated and transmitted.